Respostas

2013-09-29T19:02:04-03:00
 x^{2} +x=12
 x^{2} +x-12=0 [tex] 1^{2}-4.1.(-12)
1+48
49
x= \frac{-1+- \sqrt{49} }{2.1}
x= \frac{-1+-7}{2}
x'= \frac{-1+7}{2}
x'= \frac{6}{2}
x'=3
x''= \frac{-1-7}{2}
x''= \frac{-8}{2}
x''=-4 nao convem
 3^{2}+3=12
9+3=12
12=12
R=3
 x^{2} -2x=-1
 x^{2} -2x+1=0
(-2) ^{2}-4.1.1
4-4
0
x= \frac{-(-2)+- \sqrt{0} }{2.1}
x= \frac{2}{2}
x=1
 1^{2}-2.1=-1
1-2=-1
-1=-1
r=-1
 x^{2} -2x=80
 x^{2} -2x-80=0
(-2) ^{2}-4.1.80
4+320
324
x= \frac{-(-2)+- \sqrt{324} }{2.1}
x= \frac{2+-18}{2}

x'= \frac{2+18}{2}
x'= \frac{20}{2}
x'=10
x''= \frac{2-18}{2}
x''= \frac{-16}{2}
x''=-8  nao convem
 10^{2} -2.10=80
100-20=80
80=80
RESPOSTA=10
2 5 2